Pendampingan Implementasi Integrated Crops Management (ICM) untuk Meningkatkan Produktivitas Kelompok Wanita Tani "Hasil Sepakat" di Gampong Ranub Dong, Aceh Barat : Pengabdian - Siregar, Mawaddah Putri Arisma; Itawarnemi, Hilmina; Hayuningtyas, Afwa; Emyrtha, Zhuan Anses; Hasibuan, Emrizal Sultana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to enhance the knowledge and skills of the “Hasil Sepakat” Women Farmers Group (KWT) in implementing the Integrated Crop Management (ICM) system in rice cultivation. The methods used included outreach, training, mentoring, and demonstration plots. The results showed an improvement in participants’ understanding of sustainable rice cultivation techniques, as evidenced by their active participation in discussions and their ability to apply the practical steps for producing botanical pesticides. In addition, an agricultural technology assistance package was provided to support the implementation of ICM. This activity contributed to the empowerment of women farmers and supported the regional food security program, increasing rice productivity to 8.5 tons/ha..